Analysis of Lead (Pb) Levels in Consumption Fish on the Pentadu Coast East of Gorontalo Province - Sri Layla Putri Ishak; Dewi Wahyuni K. Baderan; Syam S. Kumaji; Djuna Lamondo; Regina Valentina Aydalina (Indonesian Journal of Chemistry and Environment, 2026)
The purpose of this study was to analyze the lead (Pb) levels in fish for consumption on the East Pentadu Coast, Gorontalo Province, and to evaluate whether these levels were within the maximum limits according to the applicable quality standards. This study was conducted at three locations: the boat dock, the mangrove area, and the auction site. The method used in this study was a quantitative descriptive method using a purposive sampling technique. The population in this study included fish for consumption on the East Pentadu Coast, the muscles of which were collected at all three locations. The results showed that the highest lead levels in Cetoscarus ocellatus fish were 0.0003 mg/kg, far below the maximum limit of SNI 7387:2009, which is 0.1 mg/kg. Therefore, consumption of fish from the East Pentadu Coast is still considered safe, although the cumulative Pb properties still require vigilance.